Elektrotekhnika i elektromekhanika Ėlektrotekhnika i ėlektromekhanika = Electrical enginnering & electromechanics. - Nat͡sionalʹnyĭ tekhnichnyĭ universytet "Kharkivsʹkyĭ politekhnichnyĭ instytut" (Kharkiv : Nat͡sionalʹnyĭ tekhnichnyĭ universytet "Kharkivsʹkyĭ politekhnichnyĭ instytut", 2002)
Shchokvartalʹnyĭ naukovo-praktichnyĭ z͡hurnal.
Text in Ukrainain and Russian.
Description based on: 2003, no. 2; title from PDF article running title (journal site, viewed Dec. 3, 2014).
Latest issue consulted: 2014, no. 5 (journal site, viewed Dec. 3, 2014).
Keywords: Electrical engineering -- Periodicals; Power (Mechanics) -- Periodicals; Electric machinery -- Periodicals; Electric machinery; Electrical engineering; Power (Mechanics); Electronic journals